School Financial Management Model Based on Participation, Technology, and Continuous Evaluation - Aldi Prasetiyo; Ahmad Dzofron Abiyyu Tsaqib Muhes (proceedings.icesy, 2026)
Effective educational financing management is a critical foundation for improving school quality. This study aims to holistically analyze the synergistic interaction between active stakeholder participation, digital technology utilization, and sustainable monitoring and evaluation (M&E) implementation at SMP Terpadu Darussalam Tulungagung. Using a qualitative case study approach, data were collected through interviews, observation, and document analysis, then analyzed using the Miles and Huberman model. The results reveal that the success of financial management is not determined by a single factor, but by the dynamic interaction of all three, forming a synergistic cycle. Substantive participation builds legitimacy, digital technology enhances efficiency and transparency, while participatory M&E maintains accountability. These three components mutually reinforce each other, creating a transparent, accountable, and adaptive financial governance ecosystem. This study contributes to developing an integrative educational financial governance model that can serve as a reference for schools and policymakers.